Rapid Determination of 21 Chinese Domestically Registered Pesticides in Ginseng Using Cleanup Based on Zirconium-Oxide-Modified Silica and Ultrahigh-Performance Liquid Chromatography-Tandem Mass Spectrometry - Zhongbei Zhang; Zhou Lu; Nan Fang; Zhiguang Hou; Weiming Ren; Yueru Li; Zhongbin Lu (Journal of Analytical Methods in Chemistry)
In this study, an analytical method was developed for the rapid determination of 21 pesticides used in ginseng cultivation. All pesticides covered by this method have been registered by 2020 in China for use on ginseng. The extracts were cleaned up using zirconium-oxide-modified silica (Z-Sep) and primary secondary amine (PSA). The combination of Z-Sep and PSA provided good recovery for all analytes and the cleanest matrix background out of a number of PSA-based sorbent combinations, as indicated by high-performance liquid chromatography (HPLC) and gas chromatography (GC). Instrumental analysis was completed in 5 min using the ultrahigh-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS). The linearity (r > 0.99) for all analytes was satisfactory over the calibration range of 0.002–0.1 μg mL−1. Intraday recoveries (n = 5) at ginseng-spiked levels of 0.02, 0.05, 0.1, and 1 mg kg−1 ranged between 72% and 119%, with the corresponding relative standard deviations (RSDs), were less than 19%, while the interday recoveries (n = 15) ranged between 77% and 103%, and RSDs were less than 22%. Limits of quantitation (LOQs) ranged between 0.02 and 0.05 mg kg−1 for all 21 pesticides. This is a seminal study using Z-Sep for the efficient cleanup of ginseng samples, and it could present a practical method for future monitoring of pesticide residues in ginseng produced in China.